TRANSGENDER SURVIVAL AND ADVERSITY IN JEET THAYIL’S NARCOPOLIS - Neetu (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The transgender identity within the Narcopolis environment presents a complex dynamic marked by profound challenges. Transgender individuals navigating these settings face heightened vulnerabilities due to the prevalence of substance abuse, crime, and societal marginalization. Despite adversities, their resilience manifests in various forms, including community support networks, personal strength in the face of discrimination, activism for rights and resources, and innovative contributions to culture. Thayil presents the haunting reality of the life of marginalized and oppressed individuals. Thayil's debut novel, becoming a voice for the voiceless, this paper explores his rendition of how people survive in the margins, concealed mainly from critical scrutiny.